Dengue Virus Infections: Global Scenario, Classification, and Clinical Manifestations– A Review - Thant, Zin; Norizhar, Kadarman; Tengku Muhammad Ariff, Raja Hussin; Azmi, Hassan (2016)
This review is a describe of dengue and dengue hemorrhagic fever (DHF) based on international experience. We portray the virus characteristics and risk factors for dengue and DHF, and compare incidence and the case fatalness rates in endemic regions. The clinical depiction and the pathogenesis of the severe disease are explained. We also discuss the viral, individual, and environmental factors that determine severe disease. Much more research is obligatory to elucidate these mechanisms. Although dengue has been a public health problem for some periods, the extent of the disease affliction and epidemiological leanings remain off-color understood. Dengue is the most important arthropod-borne viral disease of humans. Its presentation is protean and varies from an undifferentiated viral syndrome to hemorrhagic fever and severe shock. Its severe forms (hemorrhagic fever and shock syndrome) may lead to multisystem involvement and death. Early diagnosis, close monitoring from worsening and response to treatment are needed in all cases. WHO has provided a stepwise strategy to management that is useful for minor forms and initial shock. In the more severe forms aggressive fluid resuscitation and support for failing organs is required for the critically ill patient. To cap it all, there is no specific therapy for dengue infections. Good supportive care may be lifesaving, but eventually initiatives intended at vector control and prevention of mosquito bites may provide the utmost benefits. The dengue case data indicate a high and increasing burden of disease. Efforts now need to focus on using available data to prompt more effective outbreak response and to guide the design and enactment of intervention strategies.